2011
DOI: 10.1111/j.1478-3231.2011.02520.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepcidin response to acute iron intake and chronic iron loading in dysmetabolic iron overload syndrome

Abstract: Background The pathogenesis of dysmetabolic iron overload syndrome (DIOS) is still unclear. Hepcidin is the key regulator of iron homeostasis controlling iron absorption and macrophage release. Aim To investigate hepcidin regulation by iron in DIOS. Methods We analysed urinary hepcidin at baseline and 24 h after a 65 mg oral iron dose in 24 patients at diagnosis and after iron depletion (n=13) and compared data with those previously observed in 23 healthy controls. Serum iron indices, liver histology and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 28 publications
0
17
0
4
Order By: Relevance
“…On the other hand, pilot studies have found high hepcidin levels in either serum [24] or urine [25] of few DIOS subjects (n = 16 to 24), suggesting a distinct pathogenesis. Supporting and extending these observations, our results establish for the first time at population level that subjects with MetS have increased serum levels of hepcidin.…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, pilot studies have found high hepcidin levels in either serum [24] or urine [25] of few DIOS subjects (n = 16 to 24), suggesting a distinct pathogenesis. Supporting and extending these observations, our results establish for the first time at population level that subjects with MetS have increased serum levels of hepcidin.…”
Section: Discussionmentioning
confidence: 96%
“…Several pathways in the liver regulate hepcidin, the master hormone for maintaining systemic iron homeostasis. Recent studies have shown that these pathways can have redundancy or act independently based on the stimuli (172). The challenge will be to understand how these pathways crosstalk and are regulated in a coordinate manner to maintain hepcidin levels.…”
Section: Resultsmentioning
confidence: 99%
“…These results have been later criticized based on contrasting findings of reduced iron absorption in still iron‐overloaded DIOS patients , with the amount of iron stores being a major confounder of iron metabolism regulation. Indeed, strong upregulation of hepcidin release when hepatic iron stores begin to accumulate may counteract the development of severe iron overload in DIOS .…”
Section: Discussionmentioning
confidence: 99%
“…Although variants in genes implicated in HH are predisposing factors , the mechanism underpinning iron accumulation in DIOS is still unclear. Previous studies indicated that circulating hepcidin concentration at diagnosis is upregulated coherently with iron stores . Conversely, HH is caused by decreased hepcidin release in response to iron overload .…”
mentioning
confidence: 98%